Estudio comparativo entre dosis equipotente de bupicaina con adición de buprenorfina vs morfina subaracnoidea en pacientes sometidos a histeroctomía abdominal en el Hospital Manuel Ygnacio Monteros de la ciudad de Loja. - Guzmán Pomaquiza, Manuel Gerardo. (2014)
A comparative prospective study Descriptive, Analytical, Single-Blind, where efficiency between equipotent doses of bupivacaine was determined by adding Buprenorphine vs subarachnoid morphine in the management of postoperative pain in patients undergoing abdominal hysterectomy was performed. 60 patients older than 18 years who underwent elective surgery , surgical anesthetic risk with ASA I- II without contraindication for lumbar puncture were investigated by dividing into two randomized groups of 30 patients each ; Group 1: Bupivacaine-Buprenorphine ( n = 30 ) , Group 2: Bupivacaine - Morphine (n = 30). Pain was assessed with the Visual Analogue Scale (VAS) at the end of the procedure, at 6.12 and 24 hours, hemodynamic variation given by TAM and the FC is recorded at 5min, 15 min and 1 hour post- puncture lumbar. Likewise, the side effects thereof were investigated. Results: The visual analogue scale (VAS ) at 6 hours, 12 hours , and 24 hours was lower in group 2 (p = < 0.0001). Nausea and vomiting was higher in group 1 with p = < 0.05. Also pruritus (33.33 % vs 80 %) was the most common side effect in group 2 ( p = < 0.001). Heart rate and mean arterial pressure at 15 min. And one hour descent was greater in group 1 with p = < 0.001 . Conclusion: It is concluded that the use of morphine with intrathecal single dose of 120 ug is more efficient for postoperative pain management in patients who undergo abdominal hysterectomy compared with Buprenorphine. KEYWORDS: Spinal anesthesia , Bupivacaine , Buprenorphine , Morphine, Pain Management, Hysterectomy .